Central odontogenic fibroma of the mandible: A case report with diagnostic considerations. (February 2016) - Santoro, Angela; Pannone, Giuseppe; Ramaglia, Luca; Bufo, Pantaleo; Lo Muzio, Lorenzo; Saviano, Raffaele
Abstract: Introduction: Odontogenic fibroma (OF), a rare odontogenic tumor of mesodermal origin, has been thought to originate from either dental follicle, periodontal ligament, or dental papilla [1]. Different studies reported high variability in the incidence rate as being between 3 and 23% of all odontogenic tumors [2, 3]. OF manifests a dual character at the histopathological examination showing odontogenic epithelial structures mimicking those observed in biopsy of ameloblastoma and, in addition, peculiar fragments of cellular stroma. The clinical and radiological features of OF are similar to other odontogenic and/or non-odontogenic tumours and the differential diagnosis may first occur at fine-needle aspiration biopsy. Presentation of case: In the case reported, a young patient showed a localized gingival enlargement involving radiologically the superior margin of the right angle of the mandible and associated with an un-erupted tooth. The morphological characteristics together with clinical and radiologic findings confirmed the tumor to be a central odontogenic fibroma (COF) with secondary gingival involvement. Discussion and conclusion: Benign odontogenic tumors may be distinguished from other odontogenic/non-odontogenic neoplasias and from malignant tumours through a cytologic differential diagnosis as treatment differs accordingly. Highlights: Attention to any gingival enlargement: it may be a clinical COF manifestation. A wrong diagnosis may determine a serious delay in patient proper treatment. It is highly recommended a periodic clinical and radiographic examination. A careful cyto-histological examination of fibrous lesions of the jaw is necessary. A proper differential diagnosis will allow the correct patient management.